Comparison of B cells' immune response induced by PEDV virulent and attenuated strains - Yuan, Chen; Zhao, Xue; Feng, Yawen; Chen, Ligong; Lin, Yidan; Li, Tanqing; Song, Qinye (Frontiers in Microbiology, 2024)
Porcine epidemic diarrhea virus (PEDV) is an acute, highly contagious enterovirus that infects pigs of all ages. The B cells are important for antigen presentation, antibody production, and cytokine secretion to resist infection. However, the role of B cells in PEDV infection remains unclear. In this study, the effects of PEDV virulent (QY2016) and attenuated strains (CV777) on B cells sorted from neonatal piglets, nursery piglets, and gilts were investigated. The results showed that PEDV-QY2016 and PEDV-CV777 could significantly increase the expression of CD54 and CD27 in B cells from neonatal piglets. The percentages of CD80, MHC II, and IgM expressed on neonatal piglet B cells infected with PEDV-QY2016 were significantly lower than those expressed on the B cells infected with PEDV-CV777. Both PEDV-QY2016 and PEDV-CV777 could stimulate IFN-α and GM-CSF secretions in neonatal piglet B cells; IL-1, IFN-α, and IL-4 secretion in nursery piglet B cells; and IL-1, TGF-β secretion, and GM-CSF in gilt B cells. Furthermore, both PEDV-QY2016 and PEDV-CV777 could induce the secretion of IgA, IgM, and IgG in nursery piglet B cells but could not induce the secretion of IgA, IgM, and IgG in neonatal piglet B cells. The secretion of IgA, IgM, and IgG was significantly higher by the PEDV-CV777 strains infected B cells than those by the PEDV-QY2016 strains infected gilt B cells. In conclusion, the surface molecule expression, cytokine secretion, and antibody production of B cells induced by PEDV are closely related to the ages of pigs and the virulence of the PEDV strain.